The effect of FDI on low and high-skilled employment and wages in Mexico: a study for the manufacture and service sectors - Eduardo Saucedo; Teofilo Ozuna; Hector Zamora (Journal for Labour Market Research, 2020)
This study analyzes the effect of Foreign Direct Investment (FDI) inflows on the employment and wages of low- and high-skilled employees in the manufacture and service sectors in Mexico. The study implements a quarterly panel dataset covering the 32 Mexican states from 2005 to 2018. The econometric model is estimated throughout Fixed-Effects (FE) and Panel Corrected Standard Errors (PCSE). Employment results indicate that an increase of FDI inflows into the manufacture sector creates a positive effect in low- and high-skilled employment. In the case of service sector, results are inconclusive across models for both categories of employment. In the case of wages, it is found that FDI inflows by the manufacture sector increase marginally in low-skilled wages and no statistical effect is captured in high-skilled wages. Lastly, in service sector, results indicate the effect of FDI inflows are inconclusive in the case of low-skilled and high-skilled wages.
Keywords: F21; F23; F36; J21; J23; R10; 330; Foreign Direct Investment; Employment; Mexico; Panel data